Effect of Zr, Zn, and Cu on Corrosion Resistance of As-Extruded Mg-3Sn-1Ca Alloy - Zheng Jia; Sichao Du; Xiaowei Niu (Crystals)
TX31 (Mg-3Sn-1Ca) is an alloy with promising future applications. This study enhances the corrosion resistance of the TX31 alloy through the addition of Zr and Zn and compares the effects of individual Cu addition and Zn/Cu composite addition on the corrosion resistance of the TX31 alloy. This study investigates the corrosion properties of TX31 alloys, focusing on the effects of the grain size, second phase, corrosion product film, and texture intensity. The addition of Zr and Zn changed the second-phase area fraction, while Cu introduced a new Mg2Cu phase. The TXZ311 alloy (Mg-3Sn-1Ca-1Zn) exhibited the best corrosion resistance, with a corrosion rate as low as 1.68 mm·year−1, a significant reduction compared to other alloys. This improvement is attributed to its higher fraction of high-angle grain boundaries (HAGBs) and the enhanced stability of the corrosion product film. The TXK311 alloy (Mg-3Sn-1Ca-1Zr) showed superior corrosion resistance, with a rate of 2.97 mm·year−1, due to its uniform and fine grain structure. In contrast, the TX31 alloy had the poorest corrosion resistance, with a corrosion rate of 3.66 mm·year−1, due to its bimodal microstructure. The addition of Cu in the TXC311 (Mg-3Sn-1Ca-1Cu) and TXCZ3111 (Mg-3Sn-1Ca-1Cu-1Zn) alloys resulted in micro-galvanic corrosion between α-Mg and Mg2Cu, which decreased the corrosion resistance.